2020
DOI: 10.3390/pharmaceutics12090833
|View full text |Cite
|
Sign up to set email alerts
|

Digital Light Processing (DLP) 3D Printing of Atomoxetine Hydrochloride Tablets Using Photoreactive Suspensions

Abstract: Three-dimensional (3D) printing technologies are based on successive material printing layer-by-layer and are considered suitable for the production of dosage forms customized for a patient’s needs. In this study, tablets of atomoxetine hydrochloride (ATH) have been successfully fabricated by a digital light processing (DLP) 3D printing technology. Initial materials were photoreactive suspensions, composed of poly(ethylene glycol) diacrylate 700 (PEGDA 700), poly(ethylene glycol) 400 (PEG 400), photoinitiator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…To date, DLP printers have been exploited to produce tablets and hydrogels containing different drugs, e.g., ATH [ 30 ], theophylline [ 27 ], ibuprofen [ 28 ], paracetamol [ 29 ] and sulforhodamine B [ 31 ], polymers/mixtures of polymers, including PEGDA, PEG 300 and PEG 400, and photoinitiators (PI) such as Irgacure 2959, riboflavin and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (DPPO). Unlike commercially available resins, when it comes to the printing of the dosage forms, it is necessary to establish optimal printing parameters for each formulation separately, in order to ensure good adhesion of the tablets to the building platform and to avoid significant variations in tablet dimensions and consequently drug loading [ 14 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, DLP printers have been exploited to produce tablets and hydrogels containing different drugs, e.g., ATH [ 30 ], theophylline [ 27 ], ibuprofen [ 28 ], paracetamol [ 29 ] and sulforhodamine B [ 31 ], polymers/mixtures of polymers, including PEGDA, PEG 300 and PEG 400, and photoinitiators (PI) such as Irgacure 2959, riboflavin and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (DPPO). Unlike commercially available resins, when it comes to the printing of the dosage forms, it is necessary to establish optimal printing parameters for each formulation separately, in order to ensure good adhesion of the tablets to the building platform and to avoid significant variations in tablet dimensions and consequently drug loading [ 14 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The working wavelength of the Wanhao Duplicator 8 3D printer used in this study is 405 nm. The same working wavelength was used in our previous studies, where the model drugs were ibuprofen [ 28 ] and ATH [ 30 ]. Both of the studies demonstrated that no drug degradation occurred during the 3D-printing process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations